Writing a Literature Review - Budhathoki, Mahendra Kumar (Cognition, 2021)
Literature review or research synthesis is an essential component in research field. Novice and student researchers usually take it as a required burden in research, and present haphazardly under sub-topics in research. There is the problem of application and correlating LR with their studies. The main purpose of this paper is to present introduction of LR/research synthesis, its functions and methods in research. LR/research synthesis consists of searching relevant literature, discussing the findings and evidence, correlating the individual studies, interpreting critically, and synthesizing them to build an argument for future research. It is a review article based on qualitative research, but not based on primary data. This paper contributes to answer the questions of writing a LR or synthesis paper, and becomes a useful reference material to novice and student researchers of higher education.